Applying Important Performance Analysis for Jabodetabek Commuter Train Services - Hermanto Dwiatmoko (International Journal of Supply Chain Management, 2020)
People's mobility in the Greater Jakarta area requires effective and efficient transportation services. At present, many modes of transportation are competing to improve the quality of services to the users, which include the commuter trains that are managed by PT. Kereta Commuter Indonesia (PT. KCI). Research is needed to determine the level of services provided by PT. KCI. Here, the researcher analyzes the effectiveness of the services of the Jabodetabek commuter train of Bogor - Tanah Abang route, especially the services at Bogor and Manggarai stations as well as on the train. The research was carried out through a questionnaire survey that produced primary data. The secondary data was obtained from PT. KCI for further processing. The method used is the validity, reliability, Importance Performance Analysis, and Normality testing by using SPSS software. The results of the research shows that PT. KCI needs to increase the number of toilets at Bogor Station, to add the first-aid kits at Bogor and Manggarai Station, to increase the number of waiting chairs at Manggarai Station, to add stairs for platforms whose height are not the same as the train floor at Manggarai Station, and to improve the performance of security officers and the awareness of the users about the use of priority passengers seats.